KELAYAKAN MULTIMEDIA INTERAKTIF BERBASIS LECTORA INSPIRE PADA MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Joni Joni; Syamswisna Syamswisna; Reni Marlina (FKIP Universitas Tanjungpura, 2020)
This research aims to determine the feasibility of interactive multimedia based on lectora inspire as a learning media on biodiversity material for class X SMA/MA. The method used in this research is descriptive method with quantitative research form. The learning media was tested for eligibility by 3 material expert validators and 3 media expert validators. Aspects judged by material experts include the format, content, and language. Aspects judged by media experts include simplicity, cohesiveness, emphasis, balance, shape and color. The material expert validators were the FKIP Untan Biology Education Study Program lecturer, the X grade SMA 1 Jongkong biology teacher and the X grade SMA 2 Jongkong biology teacher, while the media expert was the FKIP Untan Biology Education Study Program lecturer, CEO and Founder of the Borneo Animation School, and the TIK teacher SMA 1 Jongkong. The average value of the format aspect is 3.88, the content aspect is 3.73 and the language aspect is 3.83. The average value of simplicity aspects is 3.33, the integration aspect is 3.88, the emphasis aspect is 3.66, the balance aspect is 3.57, the shape aspect is 4 and the color aspect is 4. Based on the results of validation analysis, interactive multimedia lectora inspire is feasible as a learning media on biodiversity material with a total score of validation by material experts and media experts is 3.81 and 3.76 in valid categories.